2020
DOI: 10.1177/0144598720953512
|View full text |Cite
|
Sign up to set email alerts
|

Development of renewable energy multi-energy complementary hydrogen energy system (A Case Study in China): A review

Abstract: The hydrogen energy system based on the multi-energy complementary of renewable energy can improve the consumption of renewable energy, reduce the adverse impact on the power grid system, and has the characteristics of green, low carbon, sustainable, etc., which is currently a global research hotspot. Based on the basic principles of hydrogen production technology, this paper introduces the current hydrogen energy system topology, and summarizes the technical advantages of renewable energy complementary hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…The committees may raise topics of discussion about the directions of the national R&D strategy employing the nationally funded projects-based analytical information. This study can improve the limitations of previous studies [2,4,9,10,18,19,27,29,30,[32][33][34][35][36] in the following ways: the normative statement that governments should endeavor to accelerate the transition into the hydrogen economy can be empowered by the information about the public investment trends of the government, which elucidates the role of government commitment to continuous investment. The other is that the quantitative analyses, based on publications or patents alone, cannot elucidate the scale of funding and technological advancement of hydrogen-economy-related research projects.…”
Section: Potential National Collaborative Research Organizations Based On the Technology Clustersmentioning
confidence: 89%
See 3 more Smart Citations
“…The committees may raise topics of discussion about the directions of the national R&D strategy employing the nationally funded projects-based analytical information. This study can improve the limitations of previous studies [2,4,9,10,18,19,27,29,30,[32][33][34][35][36] in the following ways: the normative statement that governments should endeavor to accelerate the transition into the hydrogen economy can be empowered by the information about the public investment trends of the government, which elucidates the role of government commitment to continuous investment. The other is that the quantitative analyses, based on publications or patents alone, cannot elucidate the scale of funding and technological advancement of hydrogen-economy-related research projects.…”
Section: Potential National Collaborative Research Organizations Based On the Technology Clustersmentioning
confidence: 89%
“…The review of related literature revealed that there are two broad branches for researching the hydrogen economy. One is related to the investigation of the present status of the hydrogen economy and its roadmaps, and it recommends some policies to boost the growth of the hydrogen economy [2,4,5,9,10,18,20,27,29,30].…”
Section: Limitations Of the Research On The Hydrogen Economy And Significance Of A Systematic Framework For Implementing The Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Controlling technologies were introduced but there is a lack of research on modelling, optimization, and energy hub application. Similarly, the characteristics of energy system models and existing modelling tools together with challenges in the field of modelling and optimization of the energy systems are also introduced in the studies [6] [7]. There IJEEI ISSN: 2089-3272  An optimal schedule model of multi-energy hubs network integrating solar energy (V.V.…”
Section: Introductionmentioning
confidence: 99%